2017
DOI: 10.1021/acs.est.7b00906
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Micropollutant Removal by Activated Carbon and Porous β-Cyclodextrin Polymers under Environmentally Relevant Scenarios

Abstract: The cost-effective and energy-efficient removal of organic micropollutants (MPs) from water and wastewater is challenging. The objective of this research was to evaluate the performance of porous β-cyclodextrin polymers (P-CDP) as adsorbents of MPs in aquatic matrixes. Adsorption kinetics and MP removal were measured in batch and flow-through experiments for a mixture of 83 MPs at environmentally relevant concentrations (1 μg L) and across gradients of pH, ionic strength, and natural organic matter (NOM) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
122
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 54 publications
6
122
1
Order By: Relevance
“…We found that 1 exhibited relatively high log K D values for cationic MPs,a long with neutral compounds that bind to CDs well, which is consistent with previous reports [16,32] and observations (Figure 3). [13,17] All 18 cationic substances exhibited log K D values greater than 2on polymer 1.Incontrast, 21 of 25 anionic substances and all 10 anionic PFASs exhibited relatively low log K D values between À0.5 and 1.0 on polymer 1.These low affinities make polymer 1 an ineffective adsorbent for most anionic MPs at environmentally relevant concentrations and economically reasonable doses of 1.Incontrast, polymer 2 strongly binds anionic substances,with 21 of 25 exhibiting log K D values > 2.6 and all ten anionic PFASs exhibiting log K D values between 2.8-4.0. However,p olymer 2 binds cationic MPs more weakly with log K D values for 16 of 18 cationic MPs between À0.5-1.5.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 4 more Smart Citations
“…We found that 1 exhibited relatively high log K D values for cationic MPs,a long with neutral compounds that bind to CDs well, which is consistent with previous reports [16,32] and observations (Figure 3). [13,17] All 18 cationic substances exhibited log K D values greater than 2on polymer 1.Incontrast, 21 of 25 anionic substances and all 10 anionic PFASs exhibited relatively low log K D values between À0.5 and 1.0 on polymer 1.These low affinities make polymer 1 an ineffective adsorbent for most anionic MPs at environmentally relevant concentrations and economically reasonable doses of 1.Incontrast, polymer 2 strongly binds anionic substances,with 21 of 25 exhibiting log K D values > 2.6 and all ten anionic PFASs exhibiting log K D values between 2.8-4.0. However,p olymer 2 binds cationic MPs more weakly with log K D values for 16 of 18 cationic MPs between À0.5-1.5.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1,2] Concerns about their negative effects on human health [3][4][5][6][7] and the environment [8][9][10] motivate the development of technologies that remove MPs more effectively. [11][12][13][14][15][16] These efforts are complicated by the broad range of physiochemical properties of MPs,i ncluding charge,s ize,h ydrophobicity,a nd their diverse chemical functionality. b-cyclodextrin (b-CD)-based polymers (CDPs) with aromatic crosslinkers have shown promise to remove MPs from water.…”
mentioning
confidence: 99%
See 3 more Smart Citations